Financing higher education when students and graduates are internationally mobile - Marcel Gérard; Silke Übelmesser (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
This paper aims at linking cross border mobility of students and graduates with the financing of higher education. Against the background of institutional features and empirical evidence of the European Union and Northern America, a theoretical framework is developed. This allows analyzing the optimal financing regimes for different migration scenarios, comparing them with the regimes in place and discussing possible remedies. In particular, the (optimal) sharing of education costs between students / graduates and tax-payers is studied as well as the (optimal) sharing of the tax-payers part between the various countries involved: he country which provides higher education (the host country), the country of previous education (the origin country) and possibly the countries which benefit from the improved skills of the workers. Alternative designs exhibiting potentially desirable properties are developed and policy recommendations derived.
Keywords: F22; H52; I23; 330; financing of higher education; mobility of graduates; mobility of students